2001
DOI: 10.1021/jp003980i
|View full text |Cite
|
Sign up to set email alerts
|

Classical Trajectory Study of Energy Transfer in Pyrazine−CO Collisions

Abstract: Classical trajectory calculations for collisions between vibrationally hot pyrazine (E ) 40332 cm -1 ) and room-temperature CO are compared with recent diode laser experiments. Ab initio calculations were carried out to determine parameters for the pairwise Lennard-Jones intermolecular potential. The trajectory results appear to show good qualitative agreement with preliminary experimental results. The highest ∆E collisions occur when the CO happens to lie above the pyrazine plane just as the underlying CH wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…75 Chapman and co-workers found a biexponential rotational distribution for CO following single collisions with pyrazine(E). 76,77 When they doubled the length of the CO molecule to mimic CO 2 , while preserving other potential parameters, they found reasonable agreement with the high-energy tail from pyrazine(E)/CO 2 collisions.…”
Section: Discussionmentioning
confidence: 83%
“…75 Chapman and co-workers found a biexponential rotational distribution for CO following single collisions with pyrazine(E). 76,77 When they doubled the length of the CO molecule to mimic CO 2 , while preserving other potential parameters, they found reasonable agreement with the high-energy tail from pyrazine(E)/CO 2 collisions.…”
Section: Discussionmentioning
confidence: 83%
“…Much work has also gone into developing the theory to explain energy transfer processes. This effort includes classical trajectory studies, [17][18][19][20][21][22] and quantum-scattering studies. 21 Of particular importance to the work reported here are trajectory studies of Lendvay and co-worker 17,20 and the work of Clary et al 21 They conclude that low-frequency donor vibrational modes, with out-of-plane-type motions, are more efficient at transferring large amounts of energy in collisions.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of pyrazine-CO energy transfer [117], Chapman and co-workers showed that the initial rotation of energy acceptor CO molecules has effect on the relaxation of pyrazine vibrational energy. The increase of initial CO rotation results in an increasing fraction of energy-up collisions and an increasing average energy in the energy-up collisions.…”
Section: Effects Of Initial Rotational Temperaturementioning
confidence: 99%